2021
DOI: 10.1186/s13063-021-05177-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the combination of automated peripheral mechanical stimulation and physical exercise on aerobic functional capacity and cardiac autonomic control in patients with Parkinson’s disease: a randomized clinical trial protocol

Abstract: Background Automated peripheral mechanical stimulation (AMPS) has been proposed as a new complementary therapy with potential for improving motor and cardiovascular abnormalities in Parkinson’s disease (PD). However, AMPS long-term effects and its combination with physical exercise are unknown. Thus, this study aims to compare the effects of a program of 12 weeks of physical exercise with a 12-week intervention program combining physical exercise and AMPS on the aerobic capacity, cardiac autono… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Based on this concept, this study aimed to com-bine exercise therapy with treadmill training. in addition, despite the fact that previous studies showed the positive effects of training on Pd [12][13][14], symptoms vary from person to person, so questions remain as to what type of exercise is appropriate for the personal rehabilitation of patients with Pd [26]. Therefore, changes and trends in individual data over the course of an intervention require clarification in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this concept, this study aimed to com-bine exercise therapy with treadmill training. in addition, despite the fact that previous studies showed the positive effects of training on Pd [12][13][14], symptoms vary from person to person, so questions remain as to what type of exercise is appropriate for the personal rehabilitation of patients with Pd [26]. Therefore, changes and trends in individual data over the course of an intervention require clarification in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the purpose of this review is to rigorously analyze the existing scientific literature on AMPS interventions in individuals with Parkinson's disease, with a primary focus on both functional performance and gait biomechanics. By synthesizing and critically evaluating the findings from relevant studies, this review aims to provide a scientifically robust assessment of the efficacy and potential mechanisms of AMPS in improving gait disturbances in PD [12] . Furthermore, we intend to identify research gaps and methodological limitations in the current body of literature, as well as propose avenues for further investigation.…”
Section: Introductionmentioning
confidence: 99%